ANALISIS ASAM LEMAK BEBAS DAN NILAI DOBI PADA MINYAK SAWIT MENTAH (CPO) SETELAH PROSES APLIKASI KOMBINASI BENTONIT DAN MAGNESIUM OKSIDA (MgO) - Raja, Pada Mulia; Adlyansyah, Adlyansyah (Jurnal Agro Fabrica, 2021)
Bentonite and Magnesium Oxide (MgO) are adsorbents that can be combined applied in Crude Palm Oil (CPO) to reduce its free fatty acids (FFA) content. The quality standard of Crude Palm Oil (CPO) in SNI 01-2901-2006 is the content of FFA, water and impurities, respectively, a maximum of 5%, 0.25% and 0.25%. Another parameter which determines the quality of CPO is the deterioration of bleachability index (DOBI). The purpose of this study was to determine the ability of the combination of bentonite and magnesium oxide (MgO) to reduce levels of FFA and increase the value of DOBI. The stages of this research are: 1). Natural bentonite preparation and activation 2). The variations in the combination of Bentonite and Magnesium Oxide (MgO) are Bentonite: MgO (1: 1), Bentonite: MgO (3: 1), and Bentonite: MgO (1: 3) 3). Application of combination of Bentonite and Magnesium Oxide (MgO) on CPO and 4). Analysis of free fatty acid levels and the value of DOBI in CPO. The results showed that the best FFA reduction is on the combination of Bentonite: Mg O (3: 1) was 2.95% (according to SNI 01-2901-2006) while the highest DOBI value was shown in the Bentonite: MgO treatment (1:3) namely 2.79 (according to SNI 01-2901-2006). The combination of Bentonite: MgO can reduce the value of free fatty acids where the initial value of FFA = 5.2 after treatment, the value of FFA is 2.95% and increase the value of DOBI in CPO where the initial DOBI value is 1.65 and after treatment becomes 2.79.